2006
DOI: 10.1007/s11071-006-9125-x
|View full text |Cite
|
Sign up to set email alerts
|

New tuning rules for fractional PIα controllers

Abstract: This paper describes a new tuning method for fractional PI α controllers. The main theoretical contribution of the paper is the analytical solution of a nonlinear function minimization problem, which plays a central role in deriving the tuning formulae. These formulae take advantage of the fractional order α to offer an excellent tradeoff between dynamic performances and stability robustness. Finally, a position control is implemented to compare laboratory experiments with computer simulations. The comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 14 publications
(20 reference statements)
0
53
0
Order By: Relevance
“…These methods mainly concern the phase margin, gain margin, gain crossover frequency, and dominant poles. The studies of analytical tuning for FOPID can be found in [25][26][27]. The available rule-based methods can also be extended to the auto-tuning method by incorporating an additional test such as relay feedback test into the loop [28,29].…”
Section: Fractional Order Pid Tuning Methodsmentioning
confidence: 99%
“…These methods mainly concern the phase margin, gain margin, gain crossover frequency, and dominant poles. The studies of analytical tuning for FOPID can be found in [25][26][27]. The available rule-based methods can also be extended to the auto-tuning method by incorporating an additional test such as relay feedback test into the loop [28,29].…”
Section: Fractional Order Pid Tuning Methodsmentioning
confidence: 99%
“…Normally heuristic methods are reported for adjusting the parameters in order to achieve a convenient performance, for instance, as the heuristic method in [51] used in this paper. The design of  PI controllers follows the tuning rules in [51].…”
Section: Fractional-order Controllersmentioning
confidence: 99%
“…Although applications and design methods regard mainly on linear systems, it is possible to use some of the knowledge already attained to envisage it on nonlinear systems, since the performance of fractional-order controllers in the presence of nonlinearity is of great practical interest (Barbosa et al, 2007). In order to examine the ability of fractional-order controllers for the variable-speed operation of wind turbines, this book chapter follows the tuning rules in (Maione & Lino, 2007). But, a more systematic procedure for controllers design needs further research in order to well develop tuning implementation techniques (Chen et al, 2009) for a ubiquitous use of fractional-order controllers.…”
Section: Fractional Order Controllersmentioning
confidence: 99%
“…An important property revealed by the Riemann-Liouville and Grünwald-Letnikov definitions is that while integer-order operators imply finite series, the fractional-order counterparts are defined by infinite series (Calderón et al, 2006), (Arijit et al, 2009 A good trade-off between robustness and dynamic performance, presented in (Maione & Lino, 2007), is in favour of a value for μ in the range [0.4, 0.6].…”
Section: Fractional Order Controllersmentioning
confidence: 99%
See 1 more Smart Citation